2020
DOI: 10.3390/cancers12061658
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Central Lymph Node Dissection Improves Disease-Free Survival in Patients with Intermediate and High Risk Differentiated Thyroid Carcinoma: A Retrospective Analysis on 399 Patients

Abstract: The role of prophylactic central lymph node dissection (pCLND) in the treatment of differentiated thyroid cancer (DTC) is controversial and still a matter of debate. The primary outcome of our study was to assess whether pCLND is effective in reducing the incidence of recurrent disease, and the secondary goal was to estimate the incidence of postoperative complications in patients who underwent pCLND and to evaluate the prognostic value of occult node metastases. In this retrospective study, we included patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 36 publications
3
36
0
Order By: Relevance
“…PTC is currently considered to be a low-risk malignancy with a good prognosis worldwide; however, CLNM and postoperative recurrence can reduce the disease-free survival (DFS) in patients with PTC [ 21 , 32 , 33 ]. Studies have confirmed that there are 20%–25% probabilities that PTC can occur with con-CLNM [ 15 , 17 ]; bilateral CLND in advanced PTC has shown an improved DFS rate and reduced risk of recurrence [ 34 , 35 ], though controversy exists in whether contralateral prophylactic CLND should be carried out in uni-PTC and advanced PTC [ 13 , 14 ]. The incidence of residual nodal metastases in the contralateral central neck compartment was 14.3%–23.0% in PTC patients who underwent ipsilateral CLND, which was significantly higher than in those who underwent bilateral CLND [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…PTC is currently considered to be a low-risk malignancy with a good prognosis worldwide; however, CLNM and postoperative recurrence can reduce the disease-free survival (DFS) in patients with PTC [ 21 , 32 , 33 ]. Studies have confirmed that there are 20%–25% probabilities that PTC can occur with con-CLNM [ 15 , 17 ]; bilateral CLND in advanced PTC has shown an improved DFS rate and reduced risk of recurrence [ 34 , 35 ], though controversy exists in whether contralateral prophylactic CLND should be carried out in uni-PTC and advanced PTC [ 13 , 14 ]. The incidence of residual nodal metastases in the contralateral central neck compartment was 14.3%–23.0% in PTC patients who underwent ipsilateral CLND, which was significantly higher than in those who underwent bilateral CLND [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical community has reached a general consensus that central lymph node dissection (CLND) for therapeutic purposes is appropriate in PTC patients with suspected cervical lymph node metastasis (LNM) (5). By contrast, however, there is a growing controversy over the role of prophylactic central lymph node dissection (pCLND) due to the lack of randomized controlled data (6)(7)(8). Generally speaking, pCLND is not recommended for a subset of patients with small (T1 or T2), non-invasive, clinically node-negative (cN0) PTC according to the 2015 American Thyroid Association (ATA) guidelines (9), whereas the Japanese Society of Thyroid Surgery and the Chinese Thyroid Association both strongly recommend routine pCLND for cN0 PTC patients in order to stage disease and prevent recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…The study by these researchers found that cervical lymph node metastases conferred an increased risk of death in all patients with follicular carcinoma and in those patients with PTC who were > 45 years old ( 8 ). A retrospective analysis of 399 patients demonstrated that prophylactic central compartment (level VI) neck dissection (CCND) improved disease-free survival in patients with intermediate- and high-risk differentiated thyroid carcinoma ( 9 ).…”
Section: Introductionmentioning
confidence: 99%